Synthesis of waterborne polyurethane by inserting polydimethylsiloxane and constructing dual crosslinking for obtaining the superior performance of waterborne coatings. (1st June 2022) - Li, Fuqiang; Liang, Zhong; Li, Yuxing; Wu, Zhimin; Yi, Zhengming
Abstract: Polydimethylsiloxane (PDMS) is usually used to obtain favorable performances of waterborne polyurethane (WPU) such as higher hardness, exceptional thermal stability and lower interfacial tension. However, there is always a problem that waterborne polyurethane (WPU) often performs weak tensile strength, lower tenacity and brittle property at room temperature when polydimethylsiloxane (PDMS) is embedded into the backbone of polyurethane. The study aims to address the problem by constructing dual crosslinking structure, namely introducing trimethylolpropane as an intramolecular crosslinking agent into prepolymers and then adding waterborne polycarbodiimide (SK-400) as a post-crosslinking agent in order to further enlarge the degree of crosslinking and mainly make up for the shortcoming that mechanical property decreases when polydimethylsiloxane (PDMS) was inserted into molecule chains. Initially a novel inner-crosslinking prepolymer (SiWPU) comprising polydimethylsiloxane need to be synthesized successfully by inserting trimethylolpropane into prepolymers. Then the sample SiWPU-3 was picked out as a matrix resin and dropwise added polycarbodiimide (SK-400) as a post-crosslinking agent into the matrix resin (C–SiWPU). As pH was gradually lowering following the evaporation of triethylamine in the emulsion (C–SiWPU), carboxyl groups (COOH) in prepolymers started to react with SK-400 (NCN) to form twofold crosslinking structure. When 0%, 2%, 4%, 6%, and 8 wt% of waterborne polycarbodiimide (SK-400) was incorporated into the solution, the tensile strengths are 47.8 MPa, 57.7 MPa, 65 MPa, 57.6 MPa and 54.5 MPa and the elongation at break 732%, 756%, 798%, 707% and 700%. The crosslinking density of SiWPU-3 without the addition of waterborne polycarbodiimide (SK-400) is 3.86 × 10 −3 mol/cm 3 . As 6 wt% of waterborne polycarbodiimide (SK-400) was added into the emulsion of SiWPU-3, the crosslinking density of C–SiWPU-6 (6 wt% SK-400) is 6.19 × 10 −3 mol/cm 3 . The films show excellent extensibility and exceptional tenacity. Hence, the emulsion is able to be applied in leather industry. Graphical abstract: Image 1 Highlights: Tensile strength and tenacity of the films is enhanced sharply by dual crosslinking structure. The surface roughness can be erased by waterborne polycarbodiimide as a post-crosslinking agent. The coatings have a potential value in leather industry.